ADAMTS5 promotes murine adipogenesis and visceral adipose tissue expansion - Bauters, Dries; Scroyen, Ilse; Deprez-Poulain, Rebecca; Lijnen, H. Roger (Thrombosis and Haemostasis, 2016)
Enhanced expression of the aggrecanase ADAMTS5 (A Disintegrin And Metalloproteinase with Thrombospondin type 1 motifs; member 5) has been observed in adipose tissue (AT) of obese rodents. Here, we have investigated the role of ADAMTS5 in adipogenesis, AT expansion and associated angiogenesis. In vitro differentiation of precursor cells into mature adipocytes was studied using murine embryonic fibroblasts (MEF) derived from wild-type (Adamts5+/+) and ADAMTS5 deficient (Adamts5-/-) mice, or 3T3-F442A preadipocytes with stable gene silencing of Adamts5. De novo adipogenesis was monitored by injection of 3T3-F442A cells with or without Adamts5 knockdown in Nude mice. Furthermore, Adamts5+/+ and Adamts5/- mice were kept on a high-fat diet (HFD) to monitor AT development. Adamts5-/- MEF, as well as 3T3-F442A preadipocytes with Adamts5 knockdown, showed significantly reduced differentiation as compared to control cells. In mice, de novo formed fat pads arising from 3T3-F442A cells with Adamts5 knockdown were significantly smaller as compared to controls. After 15 or 25 weeks on HFD, total body weight and subcutaneous AT weight were similar for Adamts5++/+ and Adamts5-/- mice, but visceral/gonadal fat mass was significantly lower for Adamts5-/-mice. These data were confirmed by magnetic resonance imaging. In addition, the blood vessel density in adipose tissue was higher for Adamts5-/- mice kept on HFD. In conclusion, our data support the concept that ADAMTS5 promotes adipogenesis in vitro and in vivo, as well as development of visceral AT and associated angiogenesis in mice kept on HFD.
Keywords: Adipogenesis; adipose tissue; obesity; ADAMTS5; aggrecanase